UNEMPLOYMENT CRISIS AND GOVERNMENT POLICY RESPONSE: A STUDY OF N-POWER PROGRAMME - NWOGBO, DAVID C.; UGWUIBE, CHRISTOPHER ONYEMAECHI; ULOKO , OMONIGHO LISA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
The aim of the study is to identify the implications of unemployment crisis to youths’ empowerment in Nigeria, find out the extent to which government employment policy response through N-Power Programme has reduced unemployment in the country and to suggest other ways of strengthening N power programme as well as creating employment in the country. The study was conducted in three states of Nigeria namely Edo, Lagos and Kogi States. A total of 510 participants and beneficiaries of N-power programme from batch A-C were purposively selected to take part in the research. Descriptive statistical research tools such as frequency, table and percentage were used to analyze the data collected. Hypotheses were tested using Chi- Square. Findings of the study revealed that unemployment crisis in the country hinders youths’ empowerments in Nigeria as the trend makes youths to engage in all forms of social vices in order to make a living. Government employment policy response through N-Power Programme helped Nigerian youths who are beneficiaries to improve their standard of living by empowering them to make investment. Despite the success of the programme, it did not reduce unemployment rate in the country. The study recommended that government should recruit more unemployed graduates in the N-power programme